PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN GUMITIR (Tagetes erecta L) - I Made Suryana; Cokorda Javandira; I Ketut Sumantra; Stefanus Bebo (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
This research is entitled Effect of Planting Media on growth and yield of gumitir ( Tagetes erecta L ). The purpose of this study was to determine the effect of growing media on the growth and yield of gumitir plants. This research was carried out from May 25 until August 31, 2022, this study used a randomized block design (RAK) with six treatment levels, namely (M0) 5 kg of soil media, (M1) 2.5kg of soil media and 2.5kg of sand, (M2) 2.5kg of soil media and 2.5kg of wood sawdust, (M3) 2.5kg of soil media and 2.5kg of burnt husk, (M4) 2.5kg of soil media and 2.5kg of cocopeat, (M5) 2.5kg of soil media and 2.5kg of cow manure, and each treatment was repeated 4 times. The results of this study planting media gave a very significant effect on the parameters of plant height, number of branches, plant stem diameter, total flower harvest per plant, total flower fresh weight per plant, total plant fresh weight, total flower oven dry weight on plants, dry weight total plant oven, except for the number of leaves and the age of flowering gave no significant effect. The treatment that gave the best growth and yield on a mixed planting medium of soil and roasted husk (1:1) with the results: the total number of flowers harvested per plant 26.25 pcs, total flower fresh weight per plant 192.57 g, and total flower oven dry weight. per plant 17.72 g